Immunoregulatory effects of RGMb in gut inflammation - Pérez-Cruz, Magdiel; Iliopoulou, Bettina P.; Hsu, Katie; Wu, Hsin-Hsu; Erkers, Tom; Swaminathan, Kavya; Tang, Sai-Wen; Bader, Cameron S.; Kambham, Neeraja; Xie, Bryan; Dekruyff, Rosemarie H.; Freeman, Gordon J.; et al. (Frontiers in Immunology, 2022)
Graft-versus-host disease (GvHD) is a major complication after allogeneic hematopoietic cell transplantation (HCT). Current strategies to prevent GvHD with immunosuppressive drugs carry significant morbidity and may affect the graft-versus-tumor (GVT) effect. Inflammatory bowel disease (IBD) is an intestinal inflammatory condition that affects more than 2 million people in the United States. Current strategies to prevent colitis with immunosuppressive drugs carry significant morbidity. Recently, Repulsive Guidance Molecule b (RGMb) has been identified as part of a signaling hub with neogenin and BMP receptors in mice and humans. In addition, RGMb binds BMP-2/4 in mice and humans as well as PD-L2 in mice. RGMb is expressed in the gut epithelium and by antigen presenting cells, and we found significantly increased expression in mouse small intestine after total body irradiation HCT conditioning. We hypothesized that RGMb may play a role in GvHD and IBD pathogenesis by contributing to mucosal inflammation. Using major-mismatched HCT mouse models, treatment with an anti-RGMb monoclonal antibody (mAb) that blocks the interaction with BMP-2/4 and neogenin prevented GvHD and improved survival compared to isotype control (75% versus 30% survival at 60 days after transplantation). The GVT effect was retained in tumor models. Using an inflammatory bowel disease dextran sulfate sodium model, treatment with anti-RGMb blocking monoclonal antibody but not isotype control prevented colitis and improved survival compared to control (73% versus 33% at 21 days after treatment) restoring gut homeostasis. Anti-RGMb mAb (9D1) treatment decreased IFN-γ and significantly increased IL-5 and IL-10 in the gut of the treated mice compared to the isotype control treated mice.